161k views
2 votes
Find the product of (3x - 2)and(6x + 1)

User Svineet
by
5.5k points

2 Answers

1 vote

Answer:

18x² - 9x - 2

Explanation:

Each term in the second factor is multiplied by each term in the first factor, that is

3x(6x + 1) - 2(6x + 1) ← distribute both parenthesis

= 18x² + 3x - 12x - 2 ← collect like terms

= 18x² - 9x - 2

User Savvybug
by
6.2k points
4 votes

Use foil (first, outer, inner, last)

First terms: 3x * 6x = 18x²

Outer terms: 3x * 1 = 3x

Inner terms: -2 * 6x = -12x

Last terms: -2 * 1 = -2

Put all that together to get 18x² + 3x - 12x - 2

3x and -12x can be combined because they're like terms; 3x - 12x = -9x

So the final product is 18x² - 9x - 2

User ITSrAVIE
by
5.6k points